A calibration system of resonant high-acceleration and metrological traceability. (4th October 2021) - Zhai, Guodong; Yang, Xing; Lv, Qi
Abstract: Acceleration sensor is usually used to test the performance of equipment under high-acceleration vibration. It is widely used in aero-engine, steam turbine and other equipment working in high-acceleration vibration environment. Calibration is an important means to ensure the accuracy and reliability of the measurement results of the acceleration sensor. Aiming at the conventional intermediate frequency (IF) calibration system using many instruments and complicated operation, this paper designs a resonant high-acceleration calibration system based resonant beam. First, the system amplifies the acceleration amplitude through the resonance of the resonant beam at the natural frequency, thereby generating high-acceleration values to calibrate the sensor. Then the vibration control algorithm of the calibration system is optimized, and the stability of the system is verified through experiments. Finally, the communication between the upper and lower computers is carried out in the vibration control system and the laser measurement system, and the metrological traceability is realized. The experimental results show that the system can effectively calibrate the sensitivity amplitude and phase of high-acceleration sensor in the frequency range of 100–2148 Hz and the acceleration range of 50–11 853 m s −2 . This calibration system is of great significance to the research on the calibration of IF acceleration sensor.